Compensation Mechanisms for Early Maturity and High Yield in Tartary Buckwheat (Fagopyrum tataricum): A Study on ‘Source–Sink’ Relationship and Phosphorus Utilization - Xuling Chen; Li Yang; Chunxia Zhao; Shunjiang Zhao; Ziye Meng; Xiaona Zhang; Qijiao Chen; Kesu Wei; Dabing Xiang; Yan Wan; Yu Fan; Yan Wang; et al. (Agronomy)
The regulatory mechanisms underlying the ‘source–sink’ relationship in Tartary buckwheat remain largely unexplored. This study selected an early-maturing, high-yield variety, ‘Zhukuzao1’ (ZKZ1), to delve into the ‘source–sink’ relationship and the regulatory mechanisms of phosphorus utilization. Compared with Jinqiao2 (JQ2), ZKZ1 matured approximately 10 days earlier, with significantly reduced chlorophyll content, net photosynthetic rate, and down-regulated PSI-III and GBSSI, indicating a reduced ‘source’. However, ZKZ1 maintained soluble sugar levels in upper leaves and increased sugar transport to seeds, promoting plant growth and yield formation. Under varying phosphorus conditions, ZKZ1 exhibited significantly higher total phosphorus content in lower (3.9~4.5-fold) and upper (1.4~1.6-fold) leaves of seedlings, along with increased phosphorus transport to upper leaves and seeds, and up-regulated PHO1 (2.4~3.0-fold), SPX3 (1.8~2.8-fold), PAP2 (2.8~7.7-fold), and 5PTase2 (1.4~3.5-fold) in leaves, indicating improved phosphorus absorption, transport, and remobilization. At maturity, ZKZ1 achieved yields comparable to JQ2, with superior quality traits, including significantly increased contents of protein (glutenin, prolamin, and globulin) and flavonoids under normal phosphorus conditions. Notably, the efficient phosphorus-regulated sugar metabolism in ZKZ1 maintains yield via enhanced ‘flow’ despite photosynthesis decrease. This study highlights the potential of optimizing the ‘source–sink’ relationship and phosphorus utilization in early-maturing, high-yield Tartary buckwheat breeding.